Proteomics Analysis Reveals the Molecular Mechanism of MoPer1 Regulating the Development and Pathogenicity of Magnaporthe oryzae - Chen, Yue; Wu, Xiyang; Chen, Chunyan; Huang, Qiang; Li, Chenggang; Zhang, Xin; Tan, Xinqiu; Zhang, Deyong; Liu, Yong (Frontiers in Cellular and Infection Microbiology, 2022)
Glycosylphosphatidylinositol (GPI) anchoring the protein GPI modification post-transcriptionally is commonly seen. In our previous study, MoPer1, a GPI anchoring essential factor, has a critical effect on Magnaporthe oryzae growth, pathogenicity, and conidiogenesis, but its molecular mechanism is not clear. Here, we extracted the glycoproteins from the ΔMoper1 mutant and wild-type Guy11 to analyze their differential levels by quantitative proteomic analysis of TMT markers. After background subtraction, a total of 431 proteins, with significant changes in expression, were successfully identified, and these differential proteins were involved in biological regulation, as well as cellular process and metabolic process, binding, catalytic activity, and other aspects. Moreover, we found that MoPer1 regulates the expression of 14 proteins involved in growth, development, and pathogenicity of M. oryzae. The above findings shed light on MoPer1’s underlying mechanism in regulating growth, development, and pathogenicity of M. oryzae.